2016
DOI: 10.1111/izy.12125
|View full text |Cite
|
Sign up to set email alerts
|

Intensive demographic and genetic management through European Endangered Species Programmes (EEPs) can make a difference: Cherry‐crowned mangabey Cercocebus torquatus European studbook and White‐naped mangabey Cercocebus atys lunulatus EEP results

Abstract: Many species of wildlife are threatened by destruction of their natural habitat and overhunting. Breeding programmes at zoological facilities can be used to prevent the extinction of some of these species, while contributing to the maintenance of an ex situ gene pool. Two species of primates of the family Cercopithecidae, the Cherry‐crowned mangabey Cercocebus torquatus and the White‐naped mangabey Cercocebus atys lunulatus, are at risk of disappearing in their natural habitat. Populations of both species are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Supported by the West African Primate Conservation Action (WAPCA) in Ghana and Côte d’Ivoire since 2010, the first research outcomes obtained consisted of a population viability analysis (PVA) simulating different scenarios combining deterministic and stochastic factors potentially affecting white-naped mangabey wild populations’ dynamics. The study concluded genetic diversity may remain high under all assumptions (> 90%) 19 , which suggested European captive mangabeys may act as an insurance population to accomplish in-situ conservation goals.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Supported by the West African Primate Conservation Action (WAPCA) in Ghana and Côte d’Ivoire since 2010, the first research outcomes obtained consisted of a population viability analysis (PVA) simulating different scenarios combining deterministic and stochastic factors potentially affecting white-naped mangabey wild populations’ dynamics. The study concluded genetic diversity may remain high under all assumptions (> 90%) 19 , which suggested European captive mangabeys may act as an insurance population to accomplish in-situ conservation goals.…”
Section: Introductionmentioning
confidence: 97%
“…This information can be used to formulate recommendations to maintain a genetically-healthy population 17 with reliable reproduction and increasing group growth rates 18 . Such recommendations may involve translocations among zoological nuclei, and the objective selection of most appropriate individuals for reproduction and/or identification of related animals 19 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations